A COMPARISON OF DISCRETE TRIAL TEACHING IMPLEMENTED IN A ONE‐TO‐ONE INSTRUCTIONAL FORMAT AND IN A GROUP INSTRUCTIONAL FORMAT. (20th November 2012) - Leaf, Justin B.; Tsuji, Kathleen H.; Lentell, Amy E.; Dale, Stephanie E.; Kassardjian, Alyne; Taubman, Mitchell; McEachin, John; Leaf, Ronald; Oppenheim‐Leaf, Misty L.
<x xml:space="preserve">Abstract</x> Discrete trial teaching (DTT) is a systematic form of intervention commonly implemented with children and adolescents diagnosed with autism spectrum disorder. Experimenters and clinicians have implemented DTT in both one‐to‐one instructional formats and group instructional formats to teach a wide variety of skills to children and adolescents diagnosed with autism spectrum disorder. The purpose of this study was to compare DTT implemented in a one‐to‐one instructional format with DTT implemented in a group instructional format in order to determine which format was more effective, efficient, resulted in higher observational learning, and resulted in better maintenance when teaching a variety of expressive skills. The experimenters utilized a parallel treatment design, and the results indicated that both instructional formats were equally effective, there were mixed results in terms of maintenance and efficiency, and group instruction resulted in observational learning. Copyright © 2012 John Wiley & Sons, Ltd.